Implementasi Sistem Pendukung Keputusan Menentukan Suplier Bahan Baku Minuman Terbaik Menggunakan Metode Smart (Studi kasus Sedot.idn) - Awaludin Yusrizal; Anief Fauzan Rozi (Journal Of Information System And Artificial Intelligence, 2023)
Currently, the beverage business competition is getting tougher, making each business owner want to provide the best for customers. Sedot.idn has been doing the selection of raw material suppliers manually so that the work done is less efficient because every time there is a change in price, quality, service and delivery time, sedot.idn business owners have to calculate and re-determine the supplier they will choose. With these problems, it is deemed necessary to make it easier to make work more effective and efficient by creating a system to help Sedot.idn business actors determine the best raw material suppliers for their business with the criteria of quality, price, service, and delivery accuracy. This system will be made using the Simple Multi Attribute Rating Technique or commonly abbreviated as SMART. In this study, data collection and analysis will be carried out to draw conclusions to determine research recommendations for the best minimum raw material suppliers and produce a system that can help business actors Sedot.Idn Making a decision support system with the SMART method can help provide solutions for the head of the outlet owner in choosing the best supplier so that Sedot.idn business owners do not need to manually calculate in the supplier selection process.